(untitled) (INNOVATIVE ECONOMY, 2025)
Shmanko N.R. ARCHITECTURE OF MANAGEMENT OF RENEWABLE GENERATION FACILITIES IN THE AGRO-INDUSTRIAL COMPLEX: AN INSTITUTIONAL AND ECONOMIC MODEL FOR COORDINATING PRODUCTION AND ENERGY CONTOURS Purpose. The aim of this study is to provide a theoretical justification of the nature of managing renewable energy generation facilities in the agro-industrial sector as an integrated management process that ensures the coordination of an enterprise’s production, energy, and institutional-market components within the context of a decentralized power system and regulatory operating regimes. Methodology of research. The methodological basis of the study is a systems approach. The theoretical and methodological framework of the study is based on a combination of principles from enterprise management theory, new institutional economics, and the concept of decentralized energy. The institutional approach is used to explain the impact of the regulatory environment on the structure of managerial decisions and the boundaries of economic behavior of economic entities. The principles of systems management were used to justify the integration of energy assets into the functional architecture of the enterprise and to determine their role in ensuring the stability of the production process. The methodological tools of the study are of a conceptual and analytical nature. Methods of analysis and synthesis were applied to identify the key characteristics of renewable generation facilities and formulate a generalized managerial interpretation of them; logical generalization – to formulate the author’s definition of the essence of management; comparative analysis – to compare economic, technological, and institutional approaches to interpreting renewable energy sources; structural and functional analysis – to reveal the place of generating facilities within the internal structure of an agricultural enterprise and to justify a model for coordinating production, energy, and market circuits; and regulatory-legal analysis – to determine the institutional boundaries of management decisions within the context of current legislation and the rules governing the electricity market. Findings. A theoretical conceptualization of the management of renewable generation facilities in the agro-industrial complex has been developed as an integrated architecture for coordinating an enterprise’s production, energy, and institutional-market systems. It has been substantiated that, in the context of the decentralization of the electric power industry, the development of active consumer modes, commercial metering, and balancing, renewable generation is transforming from a supplementary element of energy supply into a structural component of the economic system of a business entity in the agricultural sector. The evolution of scientific approaches to the interpretation of renewable generation has been analyzed, and their fragmentary nature within the context of agricultural specificity has been established, which necessitates an integrated theoretical model. It has been determined that the characteristics of agro-industrial production – seasonal demand, biologically determined technological cycles, and the presence of bioenergy flows – form a multi-level management system in which technical controllability, economic rationality, and regulatory compliance must be considered as interrelated elements. Originality. An architectural management model has been developed based on the coordination of three loops: production, energy, and institutional-market. It has been demonstrated that the essence of managing renewable generation facilities in the agro-industrial complex lies not in maximizing production as an end in itself, but in ensuring system compatibility with the grid infrastructure, minimizing regulatory and market risks, and enhancing the enterprise’s energy resilience. Management principles have been formulated, among which the key ones are legal certainty, measurability, adaptability to variable generation, and process stability. Practical value. The results obtained provide a methodological foundation for further applied research into the mechanisms for integrating renewable energy generation into the production and energy systems of agricultural enterprises. Key words: renewable generation, agro-industrial complex, management, institutional architecture, prosumer, balancing, commercial metering, energy resilience, bioenergy, decentralized energy system.